Analisis Perbandingan Metode Bayesian Network dan Dempster-Shafer Pada Sistem Pakar Diagnosis Penyakit Mata - Luh Kesuma Wardhani; Rahmad Kurniawan (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2012)
There are many methods that have been used in researches of expert system for diagnosing diseases, such as Bayesian Network and Dempster-Shafer. In this research, the main aim is to compare and to analyze the expert system for diagnosing eye disesases by using Bayesian Network with the expert system for diagnosing eye disesases by using Demspter-Shafer. From testing phase, it can be concluded that there is no significant difference in accuracy value from those two methods. The diagnosis resulting from expert system using Bayesian Network obtained accuracy of 85.7%. Similar results were also obtained from expert system using Dempster-Shafer method. Nevertheless, the inference process of Dempster-Shafer method is more complicated, where there are some combination of rules that are used to combine the evidence. While using the Bayesian inference network is easier because of the structure of the Bayesian network.Keyword : Bayesian Network, Dempster-Shafer, Expert System, Eye Disease